Political Economy of Healthcare in Pakistan: Impact on Health Security and Pandemic Preparedness - Shehzad, Zeba; Majeed, Gulshan (Annals of Human and Social Sciences, 2025)
This study aims to explore the political economy of healthcare in Pakistan, focusing on how political decisions, economic constraints, and governance structures affect healthcare delivery, particularly in pandemic response. Pakistan’s healthcare system faces challenges due to underfunding, political instability, and inefficient governance, which have created disparities in healthcare access, especially in rural areas. The COVID-19 pandemic further highlighted these systemic issues, exposing the vulnerabilities in the country’s healthcare infrastructure. This qualitative research relies on secondary data, including governmental reports, academic articles, and case studies. The study analyzes these sources to understand the impact of political and economic factors on healthcare delivery and pandemic preparedness. Key findings show that underfunding, political instability, and ineffective governance significantly hinder healthcare access and quality. The pandemic exacerbated these issues, particularly in rural regions. Federal-provincial coordination was fragmented, worsening the crisis. The study recommends increasing healthcare financing, improving federal-provincial coordination, enhancing public-private partnerships, and investing in long-term healthcare infrastructure and workforce training to improve pandemic preparedness.